Analisis Tindak Tutur Lokusi dalam Video Pembelajaran Bahasa Indonesia Kelas VIII SMP pada Kanal YouTube Helza RN - Monica Anggraini Choirunisa; Lu’lu’ Nur Fadiya; Asiah Khairunnisa Azzahra; Windi Elika Sari; Rani Diah Setyaningsih; Asep Purwo Yudi Utomo; Iwan Hardi Saputro; Nurnaningsih Nurnaningsih (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Learning via YouTube is now widely practiced by educational content creators. In this case, the use of speech used in the delivery of learning should be considered. The use of speech affects the understanding of viewers or students when watching the learning video. Therefore, the purpose of this study is to find out the locutionary speech acts in the Indonesian language learning videos of class VIII SMP on Helza RN's YouTube channel and the effectiveness of the use of speech. Descriptive qualitative research method is used to analyze the related data. The approach used in this research is the theoretical approach, namely the pragmatic approach by analyzing the types of speech acts and the intentions in them. The researcher uses listening and recording techniques to find out the locution utterances in the Indonesian language learning video for class VIII junior high school on Helza RN's YouTube channel, then the researcher analyzes the speech acts related to the context with the commensurate method. From the data analysis that has been done, it is found that there are 202 declarative speech acts, 14 interrogative speech acts, and 19 imperative speech acts that make the learning video provide a complete explanation of the material, but there is a lack of interaction between Helza Rn and viewers. The results of this study are expected to increase readers' understanding of locutionary speech acts and their types. And can be a reference for other content creators, especially in making learning videos so that they are more interesting and interactive.